(The Effect of Alkalization and Roasting of Fermented and Unfermented Cacao bean on the Quality and its Flavour - Agus Sudibyo; Tiurlan F. Hutajulu; Nirwana Aprianita (Balai Besar Industri Agro, 1998)
A study on the effect of alkalization and roasting of fermented and unfermented cacao bean (Theobroma cacao, L) on the quality and its flovor had been conducted. The fermented caco bean used was taken from the estate, while unfermented cacao bean was taken from the farmer. Alkalization was carried out by using sodium and potassium carbonate at 1% and 2% concentration respectively, whereas the roasting process was done at 140 derajat celcius for 30 minutes. The analysis done on the cacao bean included pH, moisture, fat, free fatty acid (FFA), acidity and lipids composition. The result showed that quality of fermented cacao bean from the estate and unfermented cacao bean from the farmer was significantely different. The alkalization and roasting process aould improve the quality of unfermented cacao bean, however, it has affected the lipid composition.